Biodegradable Zn–3Cu and Zn–3Cu–0.2Ti alloys with ultrahigh ductility and antibacterial ability for orthopedic applications. (30th March 2021) - Lin, Jixing; Tong, Xian; Wang, Kun; Shi, Zimu; Li, Yuncang; Dargusch, Matthew; Wen, Cuie
Abstract: Zinc (Zn) and its alloys have been proposed as biodegradable implant materials due to their unique combination of biodegradability, biocompatibility, and biofunctionality. However, the insufficient mechanical properties of pure Zn greatly limit its clinical application. Here, we report on the microstructure, mechanical properties, friction and wear behavior, corrosion and degradation properties, hemocompatibility, and cytocompatibility of Zn–3Cu and Zn–3Cu–0.2Ti alloys under three different conditions of as-cast (AC), hot-rolling (HR), and hot-rolling plus cold-rolling (HR + CR). The HR + CR Zn–3Cu–0.2Ti exhibited the best set of comprehensive properties among all the alloy samples, with yield strength of 211.0 MPa, ultimate strength of 271.1 MPa, and elongation of 72.1 %. Immersion tests of the Zn–3Cu and Zn–3Cu–0.2Ti alloys in Hanks' solution for 3 months indicated that the AC samples showed the lowest degradation rate, followed by the HR samples, and then the HR + CR samples, while the HR + CR Zn–3Cu exhibited the highest degradation rate of 23.9 μm/a. Friction and wear testing of the Zn–3Cu and Zn–3Cu–0.2Ti alloys in Hanks' solution indicated that the AC samples showed the highest wear resistance, followed by the HR samples, and then the HR + CR samples, while the AC Zn–3Cu–0.2Ti showed the highest wear resistance. The diluted extracts of HR + CR Zn–3Cu and Zn–3Cu–0.2Ti at a concentration of ≤25 % exhibited non-cytotoxicity. Furthermore, both the HR + CR Zn–3Cu and Zn–3Cu–0.2Ti exhibited effective antibacterial properties against S. aureus .